English as an interference source in the acquisition of the German word order - Hinc, Jolanta (Glottodidactica, 2010)
The paper deals with the issue of the interaction of languages in a multilingual person. First, it is related to an error analysis of the word order in German which investigates the influence of English as the first foreign language with the bounded word order on German as the second foreign language with the relative bounded word order in the group of Polish high school students. Afterwards, the basic structures of German, English and Polish word order are compared to show the topological relationship between the languages.